MAIN THERAPEUTIC PRINCIPLES IN PREMENOPAUSAL WOMEN - S. N. Tolstov; I. A. Salov; V. B. Mychka; M. Yu. Kirillova; N. A. Voychenko; I. V. Kuznetsova (Российский кардиологический журнал)
The review outlines the main mechanisms of protective estrogen effects on cardiovascular system and the role of estrogen deficiency in cardiovascular disease (CVD) development. The position of the International Menopause Society (2009) on CVD in women is summarized. The importance of non-pharmaceutical measures in lifestyle modification and CVD risk factor (RF) management is discussed. The main principles of pharmaceutical treatment in premenopausal women are presented, together with the clinical evidence on mildronate in CVD prevention. The specific features of antihypertensive therapy in menopausal women are discussed. The authors justify the use of an angiotensin II receptor antagonist losartan as a first-choice medication for the management of arterial hypertension (AH) and metabolic disturbances. The role of lipid-lowering and glucose-lowering therapy is also demonstrated. Mutual efforts of cardiologists and gynecologists, together with active monitoring, are important components of RF management and primary CVD prevention in women.